2018
DOI: 10.1159/000491559
|View full text |Cite
|
Sign up to set email alerts
|

Pocket Creation Method of Endoscopic Submucosal Dissection to Ensure Curative Resection of Rectal Neuroendocrine Tumors

Abstract: Purpose: Pancreatic/gastrointestinal tract neuroendocrine neoplasm (NEN) is divided into neuroendocrine tumor (NET) and neuroendocrine carcinoma (NEC) according to the grade of malignancy, and differences are seen in clinical prognosis. NET, and rectal NET in particular, is often treated endoscopically. Endoscopic mucosal resection (EMR) was previously the main intervention for rectal NET, but EMR with a ligation device (EMR-L) and endoscopic submucosal dissection (ESD) are now also used. However, complete res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Therefore, when perform- ing endoscopic treatment, it is necessary to leave as much submucosa as possible on the side of the resected specimen. The PCM method reported by Hayashi et al in 2014 can be easily applied to traction and countertraction (8)(9)(10). Because the muscular layer is easily recognized in PCM, incisions can be made just above the muscular layer, facilitating dissection of the submucosal layer and reducing the rate of positive deep-seated margins compared to conventional ESD.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when perform- ing endoscopic treatment, it is necessary to leave as much submucosa as possible on the side of the resected specimen. The PCM method reported by Hayashi et al in 2014 can be easily applied to traction and countertraction (8)(9)(10). Because the muscular layer is easily recognized in PCM, incisions can be made just above the muscular layer, facilitating dissection of the submucosal layer and reducing the rate of positive deep-seated margins compared to conventional ESD.…”
Section: Discussionmentioning
confidence: 99%
“…A multicentered study with several endoscopists, higher sample and follow-up time is recommended to achieve more significant and generalizable results and outcomes. Variants of ESD with tunneling and pocket-creation methods might also be studied [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…PCM-ESD was first introduced by Yamamoto, et al [7][8][9]. In recent years, several studies reported the usefulness of PCM-ESD for colorectal neoplastic lesions with giant size, difficult location, different tumor types or postsurgery conditions [7,8,10,11,[18][19][20][21][22][23][24][25]. According to the experience of endoscopists, this new ESD strategy has several advantages over C-ESD.…”
Section: Discussionmentioning
confidence: 99%